Top-Down Approach Making Anisotropic Cellulose Aerogels as Universal Substrates for Multifunctionalization - Garemark, Jonas; Yang, Xuan; Sheng, Xia; Cheung, Ocean; Sun, Licheng; Berglund, Lars A; Li, Yuanyuan (ACS nano, 2020)
Highly porous, strong aerogels with anisotropic structural properties are of great interest for multifunctional materials for applications including insulators in buildings, filters for oil cleanup, electrical storage devices, etc. Contemporary aerogels are mostly extracted from fossil resources and synthesized from bottom-up techniques, often requiring additional strategies to obtain high anisotropy. In this work, a universal approach to prepare porous, strong, anisotropic aerogels is presented through exploiting the natural hierarchical and anisotropic structure of wood. The preparation comprises nanoscale removal of lignin, followed by dissolution–regeneration of nanofibers, leading to enhanced cell wall porosity with nanofibrillated networks occupying the pore space in the cellular wood structure. The aerogels retain structural anisotropy of natural wood, exhibit specific surface areas up to 247 m2/g, and show high compression strength at 95% porosity. This is a record specific area value for wood aerogels/foams and even higher than most cellulose-based aerogels for its assigned strength. The aerogel can serve as a platform for multifunctional composites including scaffolds for catalysis, gas separation, or liquid purification due to its porous matrix or as binder-free electrodes in electronics. To demonstrate the multifunctionality, the aerogels are successfully decorated with metal nanoparticles (Ag) and metal oxide nanoparticles (TiO2) by in situ synthesis, coated by the conductive polymer (PEDOT:PSS), and carbonized to yield conductive aerogels. This approach is found to be a universal way to prepare highly porous anisotropic aerogels.